Hormonal responses to a 160-km race across frozen Alaska. Issue 2 (17th July 2007) - Kraemer, W J; Fragala, M S; Watson, G; Volek, J S; Rubin, M R; French, D N; Maresh, C M; Vingren, J L; Hatfield, D L; Spiering, B A; Yu-Ho, J; Hughes, S L; et al.
Abstract : Background: Severe physical and environmental stress seems to have a suppressive effect on the hypothalamic–pituitary–gonadal (HPG) axis in men. Examining hormonal responses to an extreme 160-km competition across frozen Alaska provides a unique opportunity to study this intense stress. Objective: To examine hormonal responses to an ultra-endurance race. Methods: Blood samples were obtained from 16 men before and after racing and analyzed for testosterone, interleukin-6 (IL-6), growth hormone (GH) and cortisol. Six subjects (mean (SD) age 42 (7) years; body mass 78.9 (7.1) kg; height 1.78 (0.05) m raced by bicycle (cyclists) and 10 subjects (age 35 (9) years; body mass 77.9 (10.6) kg; height, 1.82 (0.05) m) raced by foot (runners). Mean (SD) finish times were 21.83 (6.27) and 33.98 (6.12) h, respectively. Results: In cyclists there were significant (p⩽0.05) mean (SD) pre-race to post-race increases in cortisol (254.83 (135.26) to 535.99 (232.22) nmol/l), GH (0.12 (0.23) to 3.21 (3.33) µg/ml) and IL-6 (2.36 (0.42) to 10.15 (3.28) pg/ml), and a significant decrease in testosterone (13.81 (3.19) to 5.59 (3.74) nmol/l). Similarly, in runners there were significant pre-race to post-race increases in cortisol (142.09 (50.74) to 452.21 (163.40) ng/ml), GH (0.12 (0.23) to 3.21 (3.33) µg/ml) and IL-6 (2.42 (0.68) to 12.25 (1.78) pg/ml), and a significant decrease in testosterone (12.32 (4.47) to 6.96 (3.19) nmol/l). There were no significant differences in the hormonal levels between cyclists and runners (p>0.05). Conclusions: These data suggest a suppression of the hypopituitary–gonadal axis potentially mediated by amplification of adrenal stress responses to such an ultra-endurance race in environmentally stressful conditions.